2018
DOI: 10.1111/ajco.12862
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in patients with unresected pancreatic cancer in Australia: A population‐based study of uptake and survival

Abstract: These findings highlight the need to establish referral pathways to ensure that all patients have the opportunity to discuss treatment options with a medical oncologist. This is particularly relevant for health care systems covering areas with a geographically dispersed population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…53 A different study of unresected pancreatic cancer indicated that rural living negatively impacted oncology consultation but not receipt of chemotherapy. 54 A similar pattern was also observed for radiation therapy delivery, whereby greater distance was inversely associated with radiation oncology consultation but not with receipt of therapy. 29 Our analysis is unique because it reports on .15,000 patients, combines data on both access to care and receipt of therapy, and assesses both patient-level and region-level trajectories in accessing specialized cancer care.…”
Section: Discussionsupporting
confidence: 52%
“…53 A different study of unresected pancreatic cancer indicated that rural living negatively impacted oncology consultation but not receipt of chemotherapy. 54 A similar pattern was also observed for radiation therapy delivery, whereby greater distance was inversely associated with radiation oncology consultation but not with receipt of therapy. 29 Our analysis is unique because it reports on .15,000 patients, combines data on both access to care and receipt of therapy, and assesses both patient-level and region-level trajectories in accessing specialized cancer care.…”
Section: Discussionsupporting
confidence: 52%
“…Nevertheless, differences in survival due to variation in use of chemotherapy between hospitals seem to have decreased over the study period. During the last decade, on average 34% of patients with metastatic PDAC received chemotherapy in the Netherlands compared to 17-58% [9,10,15,[19][20][21][22] reported from other countries. Between 2007-2011 and 2012-2016, an increase was observed in the use of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…14,[30][31][32] Some small studies that examined referral patterns were limited by smaller sample sizes or also encompassed cura tive management, which confused the results. 11,12 Rates of medi cal oncology consultations for noncurative pancreatic adenocar cinoma have been reported at 31% in Nova Scotia and 54% in Alberta, with older age and higher comorbidity burden associ ated with no consultation. 11,33 Our analysis adds to knowledge in this area, as it involves over 10 000 patients, combines data on both access to care and receipt of therapy, and assesses the trajectory in accessing specialized cancer care.…”
Section: Discussionmentioning
confidence: 99%